Improved study of the structure of e+e- → bb̄g events and limits on the anomalous chromomagnetic coupling of the b quark - Abe, K; Abe, K; Abe, T; Adam, I; Akimoto, H; Aston, D; Baird, K; Baltay, C; Band, H; Barklow, T; Bauer, J; Bellodi, G; et al. (2002)
The structure of 3-jet e+ e- → bb̄g events has been studied using hadronic Z0 decays recorded in the SLC Large Detector experiment at SLAC. Three-jet final states were selected and the charge-coupled-device-based vertex detector was used to identify two of the jets as b or b̄; the remaining jet in each event was tagged as the gluon jet. Distributions of the gluon energy and polar angle with respect to the electron beam were measured over the full kinematic range, and used to test the predictions of perturbative QCD. We find that beyond-leading-order QCD calculations are needed to reproduce the features seen in the data. The energy distribution is sensitive to an anomalous b chromomagnetic moment K at the bb̄g vertex. We measured κ to be consistent with zero and set 95% confidence level limits on its value, -0.06<κ<0.04. © 2002 The American Physical Society.